KSZTAŁTOWANIE UMIEJĘTNOŚCI AUTOEWALUACJI U UCZĄCYCH SIĘ JĘZYKA OBCEGO W WIEKU 55+ - Posiadała, Katarzyna (Neofilolog, 2020)
Self-assessment is a key learning strategy for autonomous language learning, enabling learners to become more aware of the learning process, more ready to take responsibility for their own learning, empowered to make their own changes and to relate learning to individual needs. Also it may help learners to become more aware of their own strengths and weaknesses, as well as of strategies which best suit their particular learning styles and hence to become more reflective and autonomous explorers of language. This paper discusses why self-assessment is important in the toolkit of foreign language learners aged 55+ and presents techniques which help develop self-assessment skills in foreign language learning in this group of learners. One of the most effective self-assessment tools in working with students aged 55+ is The European Language Portfolio.